Pelaksanaan Pengelolaan Dana Desa Secara Transparan Di Desa Pekan Kamis Kecamatan Tembilahan Hulu Berdasarkan Permandagri No 20 Tahun 2018 Tentang Pengelolaan Keuangan Desa - Hendra Gunawan; Wandi; Fitri Wahyuni (Program Studi Pascasarjana Magister Hukum Universitas Islam Indragiri, 2025)
The implementation of village management funds in Pekan Kamis Village, Tembilahan Hulu District, has not fully complied with applicable regulations. The implementation of village government accountability reports does not include details of activities development, This is certainly contrary to Regulation of the Minister of Home Affairs Number 20 of 2018 concerning on village financial managemen. The formulation of the problem in this study is, how is the implementation of transparent village fund management in Pekan Kamis Village, Tembilahan Hulu District reviewed from the Minister of Home Affairs Regulation No. 20 of 2018 concerning village financial management? What are the obstacles to the implementation of transparent village fund management in Pekan Kamis Village, Tembilahan Hulu District reviewed from the Minister of Home Affairs Regulation No. 20 of 2018 concerning village financial management. The research method used is empirical research. Purposive sampling was used for the study.Village fund management has been implemented in accordance with Home Affairs Ministerial Regulation Number 20 of 2018, Article 78, which outlines the management stages, including planning, implementation, administration, reporting, and accountability. However, the management has not been fully implemented. Research shows that the implementation has not been transparent, particularly in detailing the budget surplus (SILPA). The conclusin, Pekan Kamis Village, Tembilahahan Hulu District, has not fully implemented transparent village fund management. The Silpa fund report is not detailed, only listing the total amount of funds allocated. Community-based obstacles include a lack of understanding of the importance of understanding village finances and attending accountability meetings.